Women and Digital Literacy at the Grassroots Level - Yuyun Sunesti; Leni Winarni; Addin Kurnia Putri; Firdastin Ruthnia Yudiningrum (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2023)
Digital activities dominate the acquisition, dissemination, and reproduction of information, causing the rise of hoax information due to the lack of digital literacy and wise use of the internet. One of the steps is through Digital Literacy, one of which is on PKK cadres. They have an important role in the family and community as influential agents to spread digital literacy in the family and surrounding community. Through a service learning approach, with five stages of social planning, namely problem identification, goal setting, program planning, program implementation and program evaluation. The results of assistance through UNS cooperation in collaboration with SEAN International Deakin University Australia to PKK cadres in Pucangan Kartasura village, Sukoharjo, Central Java. The results of this community partnership program show a significant positive impact on the PKK mothers' knowledge and skills in managing information from digital sources. Improved digital literacy skills encourage mothers to become digital literacy advocates in their families and communities and become an important step in combating the spread of hoax information at the grassroots level.